2006
DOI: 10.1007/s00216-006-0655-3
|View full text |Cite
|
Sign up to set email alerts
|

Validated HPLC–MS–MS method for simultaneous determination of atorvastatin and 2-hydroxyatorvastatin in human plasma—pharmacokinetic study

Abstract: Cholesterol-reducing statin drugs are the most frequently prescribed agents for reducing morbidity and mortality related to coronary heart disease. In this publication a validated, highly sensitive, and selective isocratic HPLC method is reported for quantitative determination of the major statin drug atorvastatin (ATV) and its metabolite 2-hydroxyatorvastatin (HATV). Detection was performed with an electrospray ionization triple-quadrupole mass spectrometer equipped with an ESI interface operating in positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 10 publications
1
44
0
Order By: Relevance
“…One possibility is that AVA could act as an adjuvant therapy. Wong and Davis recently showed that AVA did not potentiate the in vitro activity of dihydroartemisinin (DHA) in the 3D7 strain of P. falciparum (13) and also posited that AVA had no clinical relevance because AVA IC 50 s were well above the plasma concentrations achievable in humans taking high-dose AVA (0.1 to 0.5 M) (2).…”
mentioning
confidence: 99%
“…One possibility is that AVA could act as an adjuvant therapy. Wong and Davis recently showed that AVA did not potentiate the in vitro activity of dihydroartemisinin (DHA) in the 3D7 strain of P. falciparum (13) and also posited that AVA had no clinical relevance because AVA IC 50 s were well above the plasma concentrations achievable in humans taking high-dose AVA (0.1 to 0.5 M) (2).…”
mentioning
confidence: 99%
“…All of these methods consisted buffers combination as mobile phase. Several methods also reported for determination of Statin's [30][31][32][33][34].…”
Section: Figmentioning
confidence: 99%
“…Some of those methods include enzyme inhibition assay [9], radioimmunoassay [10], electrochemical method [11], high-performance liquid chromatography (HPLC) with ultraviolet (UV) detection [12][13][14][15], liquid chromatography-mass spectrometry [16], microbore liquid chromatography/electrospray ionization-tandem mass spectrometry [17], and liquid chromatography-tandem mass spectrometry (LC-MS/MS) [18][19][20][21][22][23][24][25][26][27]. Immunoassay methods lack specificity and, in some cases, are subject to problems with cross-reactive interferences.…”
Section: Introductionmentioning
confidence: 99%